Review of the Leptogenys unistimulosa species group (Hymenoptera: Formicidae) with the description of a new Amazonian species - Tozetto,Leonardo (2022)
ABSTRACT Leptogenys elzasoares new species, is described from workers and a male collected near Manaus in the Brazilian Amazon. The worker is recognizable by the presence of 12 chaetae (stout setae) on the clypeal median lobe, the straight mandible, and its bicolored body; the head and mesosoma are black while the gaster is brightly ferruginous. For the first time, the males of L. bohlsi Emery, 1896, L. unistimulosa Roger, 1863, and L. parensis Lattke, 2011 are described. A new key to the males of the unistimulosa species group is provided, and the key to workers of Lattke (2011) is updated to include the new species. Finally, we also report new records of L. parensis from French Guiana, expanding the known distribution by over 780 km northwest.